Kritik Sosial Politik dalam Lakon Semar Gugat karya Nano Riantiarno - SUMPENO - (Institut Seni Indonesia Yogyakarta, 2009)
Socio-Political Critique in Nano Riantiarno’s Semar Gugat. This article discusses social critique of SemarGugat play script, various symbolism within the play, and socio-historical factors behind the writing of Riantiarno’splays. Semar Gugat is interpreted as a manifestation of Riantiarno’s critiques to social, political, economy, and lawdisparities in Indonesia. Through this play, Riantiarno criticizes the authoritarian, corrupt, and colluded politicalsystem of New Order. Semar is a manifestation of grassroots people’s struggle against an authoritarian government.